Y Shaped Colonic Duplication Mimicking Intestinal Volvulus: A Case Report and Review of Literature - Volkan Sarper Erikci (Galenos Publishing House, 2021)
Enteric duplications are rare congenital anomalies found anywhere from mouth to anus. Colonic duplications constitute about 13% of all enteric duplications. In this report a 6-year-old boy with chronic abdominal pain for a duration of last 2 years requiring intermittent hospital admissions was diagnosed as colonic duplication mimicking intestinal volvulus. Clinical findings are nonspecific and definitive diagnosis can only be made during surgical intervention and surgical treatment is advocated for all duplications. The topic is discussed under the light of relevant literature with a brief a brief literature review.